Assessing ESL Learners in Narrative Writing with Gamification through Storium: A Quantitative Study - S. Shruthi; Dr. B. R. Aravind (Recent Trends in Social Studies, 2024)
The purpose of this study was to investigate the use of the gamification approach from Storium to improve the narrative writing abilities of students learning English as a Second Language (ESL). Learners generate an interest in both studying and playing. Also, the study investigates the evaluation and practicability of gamification for English as a Second Language (ESL) students. The present study employs quantitative research method to study the findings. They range in age from 17 to 20 years old and speak five different languages as their mother tongue respectively. There were 72 participants from B.Tech who took part in this study. In the study, both the content and mechanics of narrative writing skills were evaluated. The characteristics included are sentence structure, tale grammar, story cohesiveness, vocabulary, spelling, capitalization, and punctuation. Learning through games was demonstrated to be effective in improving students' narrative writing skills, as well as their ability to learn. The research also recommends in other areas to improve and enhance their subjects from the point of view of the learner.
Keywords: ESL students; Gamification; content; engineering Students; mechanics of writing; quantitative method; storium